Peningkatan Kualitas Pembelajaran di SD Negeri 173653 Nalela Melalui Metode Belajar Tambahan - Leli Arlinawati Hia; Putra Alvindra Saragih; Hesron Haganta Sembiring; Bobby Arifman Zai; Yesika Marshanda Sihite; Atalisi Zalukhu (Lembaga Pengembangan Kinerja Dosen, 2025)
This service aims to analyze the improvement of learning quality at SD Negeri 173653 Nalela through the application of additional learning methods. This activity was carried out by HKBP Nommensen University students involved in the Community Service Practice Lecture (KPPM) program. The research method in this service is a qualitative analysis approach. To obtain the necessary data and information, observations and interviews were conducted. Information is obtained from direct observation, interviews, and also documentation in the form of photographs of activities. The results of this service show that this program has succeeded in increasing student motivation and understanding of the subject matter. In addition, the social interaction that occurs in additional learning activities creates a more supportive environment, so students feel more motivated. However, the challenges faced include the long distance between each elementary school student's home and the KPPM Group IX pokso. This additional learning work program is strongly supported by the Nalela village community as parents of children who participate in additional learning. This service suggests that the additional learning program be expanded to include more students and actively involve parents and the community. With a comprehensive approach, it is hoped that the quality of education in SD Negeri 173653 Nalela can continue to improve.